A breaking internal wave in the surface ocean boundary layer. Issue 6 (8th June 2015) - Wain, Danielle J.; Lilly, Jonathan M.; Callaghan, Adrian H.; Yashayaev, Igor; Ward, Brian
Abstract High‐temporal resolution measurements in the Labrador Sea surface layer are presented using an upwardly profiling autonomous microstructure instrument, which captures an internal wave in the act of breaking at the base of the surface mixed layer, driving turbulence levels 2–3 orders of magnitude above the background. While lower‐frequency (near‐inertial) internal waves are known to be important sources of turbulence, we report here a higher‐frequency internal wave breaking near the ocean surface. Due to observational limitations, the exact nature of the instability cannot be conclusively identified, but the interaction of wave‐induced velocity with unresolved background shear appears to be the most likely candidate. These observations add a new process to the list of those currently being considered as potentially important for near‐surface mixing. The geographical distribution and global significance of such features are unknown, and underscore the need for more extensive small‐scale, rapid observations of the ocean surface layer.